TSUNAMI HAZARD ZONE IN THE COASTAL OF PANGANDARAN REGENCY - Anas Noor Firdaus; Lulut Alfaris; Putriara Tresa Fitira; Godwin Latuputty (Aurelia Journal, 2023)
Pangandaran Regency is famous for its natural beauty and favorite tourist destination in West Java, but it also has the potential for earthquakes and tsunamis due to its proximity to the Indo-Australian plate subduction zone. Pangandaran has a history of the 7.7 magnitude earthquake with the tsunami in 2006, to anticipate it again a mapping model is needed related to the vulnerability of the tsunami disaster in Pangandaran in the form of a vulnerability map as well as conducting a survey of vulnerability locations on the coast of Pangandaran. The zoning method is described descriptively using satellite imagery and direct observation, satellite imagery data analyzed are data on slope, elevation, land use, distance from the river and distance from the coastline. The tsunami hazard along the coast of Pangandaran Regency is relatively different from one zone to another, because it is influenced by parameters of morphology, bathymetry and coastal topography. Indicators of coastal slope and bottom of coastal waters play an important role in the magnitude of the potential for a tsunami in a zone, the zoning results show that the Pangandaran coastal area may be directly affected by tsunami waves. The following are high-risk zones which are areas with low altitudes such as the sub-districts: Kertamukti, Ciparanti, Legokjawa, Cijulang, Parigi, Karangbenda, Cibenda, Sukaresik, Wonoharjo, Pananjung, Babakan and Bagolo. These sub-districts need to install signs of tsunami vulnerability in the event of an emergency, it is also necessary to conduct outreach and training on preparedness in the event such as an earthquake and natural signs related to a tsunami or post-tsunami.